2002
DOI: 10.1530/eje.0.1460559
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokines inhibit the expression and function of human type I 5'-deiodinase in HepG2 hepatocarcinoma cells

Abstract: Objective: The sick euthyroid syndrome in critically ill patients without primary disease of the thyroid gland is characterised by low serum total triiodothyronine (T 3 ), normal to elevated thyroxine (T 4 ), elevated reverse T 3 (rT 3 ) and normal TSH levels. The aim of this work was to clarify if impaired T 4 and rT 3 5 0 -deiodination is an underlying mechanism. Design and Methods: We analysed the effect of the human recombinant proinflammatory cytokines interleukin (IL)-6 and IL-1b, tumour necrosis factor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 41 publications
1
46
0
Order By: Relevance
“…It is known that LPS administration results in increased IL-12 and IL-18 expression, which subsequently synergistically enhances INFg mRNA transcription by activating Stat4 and AP-1. The enhanced IFNg mRNA expression might be responsible for decreased D1 activity in the pituitary after LPS administration, as confirmed by in vitro studies (14). Therefore, we also studied the effects of LPS on the pituitary of IFNgR 2/2 mice compared to their WT.…”
Section: Discussionmentioning
confidence: 68%
“…It is known that LPS administration results in increased IL-12 and IL-18 expression, which subsequently synergistically enhances INFg mRNA transcription by activating Stat4 and AP-1. The enhanced IFNg mRNA expression might be responsible for decreased D1 activity in the pituitary after LPS administration, as confirmed by in vitro studies (14). Therefore, we also studied the effects of LPS on the pituitary of IFNgR 2/2 mice compared to their WT.…”
Section: Discussionmentioning
confidence: 68%
“…This is probably because LPS administration induces a number of cytokines (Boelen et al 2004a) and therefore has more effect than IL-1b alone. Studies from Jakobs et al (2002) have shown that IL-1b is the most potent cytokine to induce decreased D1 mRNA Figure 3 Relative expression of TRa1 and TRa2 mRNA in HepG2 cells after 4-h incubation with medium and 10 ng/ml IL-1b with or without 30-min preincubation with (A) 5 mg/ml actinomycin D (ActD) and (B) 10 mg/ml cycloheximide (Chx). Mean valuesGS.E.M.…”
Section: Discussionmentioning
confidence: 99%
“…NTI, among others, is characterized by low serum T 3 levels and decreased liver deiodinase type 1 (D1) activity (Peeters et al 2003, Wiersinga 2005. It has been shown that proinflammatory cytokines are capable of decreasing liver D1 mRNA expression and activity (Yu & Koenig 2000, Jakobs et al 2002, via the activation of nuclear factor (NF)kB and activator protein (AP)-1 (Kwakkel et al 2006). Liver D1 is involved in the peripheral conversion of thyroxine into T 3 and decreased activity of liver D1 therefore contributes to low serum T 3 levels.…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that, together, these modifications in deiodinase expression could be a major factor involved in causing the low T3 concentration that is associated with NTIS. The trigger for these changes in deiodinase expression has been attributed to an increase in proinflammatory cytokines, which often occurs in NTIS (35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%